2014
DOI: 10.1111/1467-8578.12049
|View full text |Cite
|
Sign up to set email alerts
|

Special education in Swedish and Finnish schools: seeing the forest or the trees?

Abstract: The purpose of this research was to study the content of the work of two special education professions in Sweden, special teachers and special pedagogues. In addition, we compare their work to the work of Finnish special teachers. The Swedish participants were 74 special educators: 27 special teachers and 47 special pedagogues. The Finnish data were from an earlier study, involving 133 special teachers. Participants in both countries were approached via a questionnaire. The results show that Swedish special pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
1
15
0
5
Order By: Relevance
“…David and Kuyini (2012) found that changes in teachers' attitudes have occurred during the last decade partly due to teachers experiencing working with special needs. This is congruent with Takala and Astrid (2014) who noted similar trends among Swedish and Finnish teachers.…”
Section: The Role Of Teacherssupporting
confidence: 91%
“…David and Kuyini (2012) found that changes in teachers' attitudes have occurred during the last decade partly due to teachers experiencing working with special needs. This is congruent with Takala and Astrid (2014) who noted similar trends among Swedish and Finnish teachers.…”
Section: The Role Of Teacherssupporting
confidence: 91%
“…However, educational policies on inclusion vary from country to country (Ahsan and Sharma, 2018;Takala and Ahl, 2018). Local policy has a decisive impact; however, the broad category of SEN carries numerous legal benefits (UNESCO, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…SEN teacher training in Finland comprises theory and practice, related to individual and small-group instruction, e.g. application of various assessment tools, support in reading and writing, mathematics, and communication, but also in behavioral and socio-emotional challenges (Takala & Ahl, 2014). Respectively, Finnish class teacher training provides readiness to instruct a whole class within general education and adapt that instruction according to children's needs.…”
mentioning
confidence: 99%